Characteristics of CD4+CD25+ regulatory T cells in the peripheral circulation of patients with head and neck cancer - Schäfer, Carsten; Kim, G. G.; Albers, A.; Hörmann, Karl; Myers, E. N.; Whiteside, T. L. (British journal of cancer, 2005)
Patients with squamous cell carcinoma of the head and neck (SCCHN) have depressed antitumour immunity. The presence of CD4+CD25+ (Treg) cells in these patients might be, in part, responsible for downregulation of antitumour immune responses. To evaluate the frequency and characteristics of Treg in the peripheral circulation of patients with SCCHN, we used multicolour flow cytometry. Expression of CCR7, CD62L, ζ chain and Annexin V binding to Treg and non-Treg CD4+ lymphocyte populations were evaluated. Treg were confirmed to be Foxp3+ and GITR+. The Treg frequency was significantly elevated in patients with active disease and those with no evidence of disease (NED) following curative therapies. Both Treg and non-Treg CD4+ T cells in patients were significantly enriched in CCR7− and CD62L− cell subsets. Although Treg in patients contained a higher proportion of double negative (CCR7−CD62L−) cells, the majority of Tregs were CCR7−CD62L+. The proportion of Annexin V+CD4+ T cells was higher in patients (P<0.00005) than normal controls (NC), and Treg were significantly more sensitive to apoptosis than non-Treg in patients and NC. Expression of ζ was reduced in all subsets of CD4+ T cells obtained from patients vs NC. The data suggest that Treg in patients with SCCHN largely contain T cells with the ‘effector’ phenotype, which bind Annexin V and have low ζ expression, consistent with their activation state and a rapid turnover in the peripheral circulation.
Gesehen am 18.03.2022